Managers of Financially Distressed Firms: Villains or Scapegoats? - KHANNA, NAVEEN; POULSEN, ANNETTE B. (Journal of Finance, 1995)
ABSTRACT In this article, we provide evidence concerning the extent to which managers are to blame when their firms become bankrupt. We study a sample of firms that file for Chapter 11 and determine the actions taken by the firms' managers during the three‐year period before the filing. We compare the sample with a control sample of firms that performed better. We suggest that the comparison provides evidence on the way managers act as their firms sink into financial trouble and whether financial distress is the result of incompetence or excessively self‐serving managerial decisions or due to factors outside of management's control. We find that managers of the Chapter 11 firms and the control firms make very similar decisions and that, on average, neither set of managers is perceived to be taking value‐reducing actions. These results do not change when we control for managerial turnover or managerial ownership. We also find that when managers are replaced in firms that eventually file for Chapter 11 protection, the market does not respond positively, regardless of whether the new managers are from inside or outside the firm. Our findings suggest that when managers are blamed for financial distress, they are serving as scapegoats.